Hubungan Lingkar Skrotum Terhadap Kualitas Produksi Testis Sapi Simmental - Okwiber Handayani; dihan kurnia; Pajri Pajri Anwar (Politeknik Negeri Jember, 2017)
This research was conducted at central of artificial insemination Tuah Sakato in May 2015. The purpose of this research to know the relationship of the circumference to the scrotum on the quality of the testicles simmental bulls production. The materials used were of 13 Simmental Bulls. The parameters of research is the parameter independent in circumference the scrotum and dependent of the parameters of the volume of semen , the consistency of cement , the concentration of spermatozoa and motility spermatozoa. Regression analisys simple was used to process the data. Results showed that the relationship between scrotal circumference and semen volume with : Y = -8.965 + 0.401 X; scrotal circumference and spermatozoa concentration :Y = 1175.533 + 14.846 X; scrotal circumference with semen consistency :Y = 0.348 + -0.057 X and scrotal circumference with sperm motility with equation Y = 31.328 + 0.783 X. It can be concluded that scrotal circumference had not a significant effect (P>0.05) on consistency , concentration and sperm motility but significant (P<0.05) on semen volume.